Between state and market : essays on charities law and policy in Canada - Phillips, Jim, 1954-; Chapman, Bruce; Stevens, David P. (David Peter), 1953- (Published for the Kahanoff Foundation Non-profit Sector Research Initiative by McGill-Queen's University Press, 2001)
"Between State and Market surveys and critiques the existing literature on charities law as well as the laws themselves. The authors offer policy prescriptions for the future of an increasingly vital sector of Canadian society."--Jacket